2014
DOI: 10.1021/es5020482
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Risks of Shale Oil and Gas Development to Wildlife, Aquatic Resources and their Habitats

Abstract: Technological advances in hydraulic fracturing and horizontal drilling have led to the exploration and exploitation of shale oil and gas both nationally and internationally. Extensive development of shale resources has occurred within the United States over the past decade, yet full build out is not expected to occur for years. Moreover, countries across the globe have large shale resources and are beginning to explore extraction of these resources. Extraction of shale resources is a multistep process that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(97 citation statements)
references
References 121 publications
1
94
0
Order By: Relevance
“…With the adoption and expansion of pad drilling (2010)(2011)(2012)(2013)(2014), the number of well bores being drilled from each pad continued to increase, which reduced the land requirement per well relative to single bore pads. Although different shale plays utilize different well densities per pad, the average pad area between 2010 and 2014 in the Williston Basin (1.7 ha) is similar to the average area of shale oil and gas pads nationally (1.2-2.7 ha; Brittingham et al, 2015). Finally, the amount of land required for NOG wells showed a rapid increase beginning in 2007 and then a precipitous drop in 2014.…”
Section: Discussionmentioning
confidence: 74%
“…With the adoption and expansion of pad drilling (2010)(2011)(2012)(2013)(2014), the number of well bores being drilled from each pad continued to increase, which reduced the land requirement per well relative to single bore pads. Although different shale plays utilize different well densities per pad, the average pad area between 2010 and 2014 in the Williston Basin (1.7 ha) is similar to the average area of shale oil and gas pads nationally (1.2-2.7 ha; Brittingham et al, 2015). Finally, the amount of land required for NOG wells showed a rapid increase beginning in 2007 and then a precipitous drop in 2014.…”
Section: Discussionmentioning
confidence: 74%
“…To adequately characterize the impact of a proposed development or activity on a particular species, it is necessary to identify the relevant local population which may be impacted (Brittingham et al, 2014;Bastos et al, 2016;Brown et al, 2016). In highly fragmented landscapes, the relevant local population may be straightforward to delineate because of the geographical separation between the area affected by the development and the nearest other sites where the species may be found.…”
Section: Introductionmentioning
confidence: 99%
“…[116,159] All of this may also affect the local ecology,b ut the effects are still largely unknown, apart from afew studies.F or example,one study has suggested that specialized species and habitatsa round well pads are most at risk because of land and food-chain fragmentation. [160] It has also been found that noise pollution from compressors at well sites affects animal behavior. [161,162] Althoughs uch studies can help with mitigationp lans,c ertain activities and characteristics are unique to the regionw here shale gas extractioni st aking place,m aking it difficult to foresee all ecological impacts.…”
Section: Land Usementioning
confidence: 99%